Quality indicators for academic journals: What makes a journal trustworthy? - Paliya, Nikita; Jha, Shiva Shankar (IP Indian Journal of Anatomy and Surgery of Head Neck and Brain, 2025)
In the vast and ever-expanding landscape of academic publishing, the ability to discern the trustworthiness and quality of journals has become essential for researchers, educators, institutions, and readers alike. As academic journals serve as key platforms for sharing validated research, it is crucial that they adhere to rigorous quality standards. This review article explores the fundamental quality indicators that signal a journal’s reliability and integrity. The peer-review process is highlighted as a primary quality determinant, as it ensures that published research is critically evaluated for methodological soundness, originality, and scientific contribution. By consolidating these quality indicators, this review provides a comprehensive framework for assessing journal trustworthiness, ultimately supporting the advancement of credible and ethical scientific communication.